1989
DOI: 10.1104/pp.90.3.841
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Nonspecific Lipid Transfer Proteins in Germinating Castor Bean Seeds

Abstract: The biosynthesis of nonspecific lipid transfer proteins (nsLTPs) in germinating castor bean (Ricinus communis L.) seeds were investigated. Lipid transfer activities of ns-LTPs in the cotyledons, axis, and endosperm increased with growth after germination. The activity increases were accompanied by increased amounts of ns-LTPs in each tissue, as measured by immunoblot using anti-ns-LTP serum. These results suggest that the ns-LTPs are synthesized de novo in each tissue after germination and not activated from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our results are consistent with previous observations showing that the amount of LTP, determined by ELISA and immunoblotting methods, varies during maturation and germination of maize (Grosbois et al, 1989) bean (Tsuboi et al, 1989). These authors observed the same kinetics for LTP accumulation and enhancement of phospholipid transfer activity.…”
Section: Discussion Ltp Gene Expression 1s Temporally and Spatially Rsupporting
confidence: 83%
“…Our results are consistent with previous observations showing that the amount of LTP, determined by ELISA and immunoblotting methods, varies during maturation and germination of maize (Grosbois et al, 1989) bean (Tsuboi et al, 1989). These authors observed the same kinetics for LTP accumulation and enhancement of phospholipid transfer activity.…”
Section: Discussion Ltp Gene Expression 1s Temporally and Spatially Rsupporting
confidence: 83%
“…It is known that different isoforms of LTPs can coexist in a given plant . Furthermore, LTPs are known to exhibit post-translational modifications such as phosphorylation as in the case of LTPs from wheat and barley .…”
Section: Discussionmentioning
confidence: 99%
“…The availability of polyclonal antibodies prepared against LTPs purified from various plants or fusion proteins (105,112) has provided tools to confirm, in some cases, the nature of a putative LTP (105), to determine the LTP contents either by ELISA or Western blot (40,116), or to localize several LTPs immunohistochemically (104,112). These antibodies also helped in the isolation of cDNAs encoding plant LTPs (109,115).…”
Section: Purificationmentioning
confidence: 99%